The Urgence And Reflection Of Multicultural Islamic Education, Democracy And Human Rights In Indonesia - Abduloh, Agus Yosep; Uus Ruswandi; Erihadiana, Mohamad; Mutmainah, Naeli; Ahyani, Hisam (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The complexity of the challenges posed by teaching staff who are not ready and do not understand multicultural education today has become a major obstacle, especially in the 4.0 era as it is today. In addition, materials and resources must be free from biases, such as social class, gender, ethnicity, religion, and urban bias. Thus, authors of sources, materials, need to use the perspective of multicultural education, democracy and human rights in Era 4.0 in terms of implementing Islamic education in Indonesia. The purpose of this study is to determine the urgency and reflection of multicultural education, democracy and human rights in Indonesia, where Islamic education today continues to experience its own complexities of challenges. The results of the study show that multicultural education can be implemented for teachers, leaders, school members and campus communities who have a multicultural attitude and have the ability to properly organize Islamic education in the era 4.0 which is full of challenges. This will also be a challenge, because schools in general cannot be separated from stereotypes and prejudices that stem from a sense of primordialism, ethnicity, religion and social class. There is the Islamic concept of Rahmatan Lil 'Alamin as a solution, and also a method of paying attention to the situation in the delivery of subject matter without disturbing the students' souls.